Liquid crystal polymer resin / carbon fiber one-way belt and preparation method thereof
Through the combination of graft modified carbon fiber and liquid crystal polymer resin, the problems of uneven distribution and poor fusion degree of carbon fiber are solved, the mechanical properties and fluorescence properties of the composite material are improved, and better engineering plastic performance is achieved.
Patent Information
- Application Number
- CN202411600498.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2024-12-27
AI Technical Summary
In the preparation process of continuous carbon fiber reinforced thermoplastic unidirectional prepreg tape, the high viscosity of the thermoplastic resin matrix leads to poor fluidity and inert surface of the carbon fiber, resulting in uneven distribution of carbon fibers and poor fusion degree, affecting the mechanical properties of the composite material.
The liquid crystal polymer resin/carbon fiber unidirectional band is prepared by grafted with benzophenone groups and a liquid crystal polymer resin containing benzophenone groups, and the liquid crystal polymer resin/carbon fiber unidirectional band is prepared through interface modification technology and melt impregnation method to produce four types of bands. Styrene groups improve binding and dispersion and enhance intermolecular action through heteroatomic groups.
It improves the binding force between carbon fiber and liquid crystal polymer resin and the uniform dispersion of carbon fiber, significantly improves the mechanical properties and fluorescence properties of composite materials, reduces processing temperature and difficulty, and is better than traditional polyether ether ketone (PEEK) materials.
Smart Images

Figure SMS_11 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of liquid crystal polymer materials, and in particular to a liquid crystal polymer resin / carbon fiber unidirectional tape and a preparation method thereof. Background Art
[0002] Continuous carbon fiber reinforced thermoplastic unidirectional prepreg tape has the characteristics of high strength, high modulus and low density, which can provide excellent mechanical properties and structural stability, making it very suitable for use as lightweight and high-strength components in various products, including automotive parts, electrical and electronic components, aircraft parts, sporting goods and building materials, etc., which can reduce product weight and reduce greenhouse gas emissions during product use and transportation.
[0003] However, the thermoplastic resin matrix used in the preparation process of continuous carbon fiber reinforced thermoplastic unidirectional prepreg tape generally has high viscosity, such as polyetheretherketone (PEEK), which has poor fluidity at high temperature, and the surface of the carbon fiber itself is inert. The two are not completely impregnated, and there is weak interaction and poor fusion, which leads to uneven distribution of carbon fiber and the formation of resin-rich areas. When the external load is transmitted to the area with low fiber content, the performance advantages of the composite material will quickly fail, and the impact performance of components such as plates will also be greatly reduced. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a liquid crystal polymer resin / carbon fiber unidirectional tape, which is prepared by compositely combining modified carbon fiber grafted with benzophenone groups and liquid crystal polymer resin containing benzophenone groups, and the unidirectional tape contains tetraphenylethylene groups.
[0005] Furthermore, the structure of the modified carbon fiber grafted with benzophenone groups is shown in Formula I, and the structure of the liquid crystal polymer resin containing benzophenone groups is shown in Formula II: Formula I; Among them, the column is carbon fiber; Formula II; Among them, x=20%-50%, y=40%-70%, z=10%-20%, x+y+z=100%.
[0006] Preferably, the liquid crystal polymer resin containing a benzophenone group has a heteroatom group R in its structure, and its structure is shown in Formula III: Formula III; Among them, x=20%-50%, y=40%-70%, z=10%-20%, x+y+z=100%.
[0007] Furthermore, the heteroatom group R is selected from any one of an amino group and a sodium sulfonate group.
[0008] Furthermore, the structure of the above-mentioned liquid crystal polymer resin / carbon fiber unidirectional tape is shown in Formula IV: Formula IV; Among them, the column is carbon fiber; x=20%-50%, y=40%-70%, z=10%-20%, x+y+z=100%.
[0009] Preferably, the structure of the above-mentioned liquid crystal polymer resin / carbon fiber unidirectional tape is as shown in Formula V: Formula V; Among them, the column is carbon fiber; R is a heteroatom group; x=20%-50%, y=40%-70%, z=10%-20%, x+y+z=100%.
[0010] Preferably, the heteroatom group R is selected from any one of an amino group and a sodium sulfonate group.
[0011] A method for preparing a liquid crystal polymer resin / carbon fiber unidirectional tape comprises the following steps: S1. Preparation of modified carbon fiber grafted with benzophenone groups: surface treating the carbon fiber by interfacial modification technology to obtain a modified carbon fiber as shown in formula I; S2. Synthesis of a liquid crystal polymer resin containing a benzophenone group: preparing a low molecular weight liquid crystal polymer, and then preparing a liquid crystal polymer resin as shown in Formula II and / or Formula III by melt copolymerization; S3. Preparation of liquid crystal polymer resin / carbon fiber unidirectional tape: Liquid crystal polymer resin / carbon fiber unidirectional tape is prepared by melt impregnation method.
[0012] Furthermore, in S1, the specific steps are: S11, impregnating and cleaning the carbon fiber with a polar solvent; S12, pre-oxidizing the surface of the carbon fiber with an oxidizing solution; S13, adding a functional modifier and a catalyst to fully react to obtain modified carbon fiber.
[0013] Furthermore, in S11, the polar solvent is selected from any one of ethanol, acetone, and petroleum ether. The polar solvent can remove pollutants on the surface of the carbon fiber.
[0014] Furthermore, in S12, the oxidizing solution is selected from any one of hydrogen peroxide solution, potassium permanganate solution, and sodium hypochlorite solution. The surface of the carbon fiber after pre-oxidation treatment is relatively rough and has oxygen-containing active functional groups.
[0015] Furthermore, in S12, the concentration of the oxidizing solution is 5-10wt%.
[0016] Furthermore, in S13, the functional modifier is 4-hydroxybenzophenone.
[0017] Furthermore, in S13, the concentration of the functional modifier is 1-5 wt%.
[0018] Furthermore, in S13, the catalyst is 4-dimethylaminopyridine.
[0019] Furthermore, in S13, the amount of the catalyst used is 0.01-0.03% of the amount of the functional modifier used.
[0020] After modification, a high-temperature resistant benzene ring structure is introduced onto the surface of the carbon fiber.
[0021] Furthermore, in S2, the specific steps are: S21, using bisphenol monomers and diacid monomers as raw materials and acetate compounds as catalysts to obtain low molecular weight liquid crystal polymers through esterification reaction; S22, heating the low molecular weight liquid crystal polymer to 300-350°C to carry out melt polymerization reaction to synthesize liquid crystal polymer resin.
[0022] Furthermore, in S21, the bisphenol monomer is a mixture of 4,4-dihydroxybenzophenone and 2,7-dihydroxynaphthalene.
[0023] Furthermore, in S21, the mass ratio of 4,4-dihydroxybenzophenone to 2,7-dihydroxynaphthalene is 1:1-5.
[0024] Preferably, in S21, the mass ratio of 4,4-dihydroxybenzophenone to 2,7-dihydroxynaphthalene is 1:1-4.
[0025] Furthermore, in S21, the diacid monomer is selected from any one of terephthalic acid, 2-aminoterephthalic acid, and 2-sulfonato monosodium terephthalate.
[0026] Preferably, in S21, the diacid monomer is selected from any one of 2-aminoterephthalic acid and monosodium 2-sulfonateterephthalate.
[0027] Furthermore, in S21, the mass ratio of the bisphenol monomer to the diacid monomer is 1:1-1.5.
[0028] Preferably, in S21, the mass ratio of the bisphenol monomer to the diacid monomer is 1:1-1.2.
[0029] Furthermore, in S21, the acetate catalyst is selected from any one of calcium acetate, magnesium acetate, and zinc acetate.
[0030] Furthermore, in S21, the mass of the acetate catalyst is 0.03-0.05% of the mass of the bisphenol monomer.
[0031] Furthermore, in S21, the esterification reaction is carried out under an inert gas, and the inert gas is any one of nitrogen and argon.
[0032] Furthermore, in S21, the esterification reaction temperature is 120-150°C.
[0033] Furthermore, in S21, the esterification reaction time is 1-2 h.
[0034] Further, in S21, the esterification reaction is carried out under stirring conditions at a rotation speed of 500-100 rpm.
[0035] Furthermore, in S22, the melt polymerization reaction temperature is 300-350°C.
[0036] Furthermore, in S22, the melt polymerization reaction time is 30-60 min.
[0037] Further, in S3, the specific preparation steps are: S31, adjusting the tension roller pressure through the fiber yarn release system so that the modified carbon fiber prepared in step S1 is evenly stressed; and fully unfolding the modified carbon fiber prepared in step S1 through the fiber dispersion system and entering the fiber impregnation system; S32, adding the LCP resin and the catalyst prepared in step S2 into the resin discharging system, and heating to melt the LCP resin; S33, the molten LCP resin infiltrates into the fiber impregnation system, impregnates the modified carbon fiber, and obtains a prepreg tape; the thickness of the prepreg tape is determined by a cooling and shaping system, and then the prepreg tape is cut and rolled to obtain a liquid crystal polymer resin / carbon fiber unidirectional tape.
[0038] Further, in S31, the tension adjustment range of the fiber yarn release system is 200-400N.
[0039] Furthermore, in S31, the heating temperature of the fiber dispersion system is 120-140°C.
[0040] Furthermore, in S32, the melting temperature is 280-300°C.
[0041] Furthermore, in S32, the catalyst is a mixture of titanium tetrachloride and zinc powder.
[0042] Furthermore, in S32, the mass ratio of titanium tetrachloride to zinc powder is 1:2-2.2.
[0043] Furthermore, in S32, the amount of catalyst added is 0.01-0.015% of the mass of the LCP resin.
[0044] Further, in S33, the heating temperature of the fiber impregnation system is 280-300°C.
[0045] Furthermore, in S33, the working pressure of the cooling and shaping system is 5-10 MPa.
[0046] Furthermore, in S33, the cooling system is a gradient cooling system, the temperature gradient is 250°C, 200°C, 150°C, 100°C, 50°C, 10°C, and the insulation time is 30-60min.
[0047] The beneficial effects of the present invention are: 1) The composite unidirectional tape prepared by the present invention is prepared by using modified carbon fibers grafted with benzophenone groups and liquid crystal polymer resins containing benzophenone groups as raw materials. The benzophenone groups on the modified carbon fibers react with the benzophenone groups on the liquid crystal polymer resin to generate tetraphenylethylene groups. On the one hand, the interaction of benzophenone enhances the binding force between the modified fibers and the liquid crystal polymer resin, improves the degree of impregnation, and thus increases the degree of fusion; on the other hand, the generated tetraphenylethylene groups have a large steric hindrance, which improves the uniform dispersion of the carbon fibers in the resin to a certain extent, reduces the formation of resin-rich areas, and effectively improves the mechanical properties of the unidirectional tape; in addition, the formation of tetraphenylethylene groups gives the unidirectional tape certain fluorescent properties.
[0048] 2) The present invention prepares a high-polymerization degree LCP resin through a two-step polymerization reaction. In the process of synthesizing the rigid chain of the LCP resin, a heteroatom group is introduced into the polymer chain through molecular structure design, which can produce a strong intermolecular effect with the group on the modified carbon fiber, and at the same time significantly improve the melting temperature and fluidity of the resin, and reduce the processing temperature and difficulty of the composite material. The rigid benzene ring structure on the polymer molecular chain gives the material excellent high temperature resistance and chemical stability, and its comprehensive performance is better than the current special engineering plastic polyetheretherketone (PEEK), and the cost is more economical.
[0049] 3) In the process of preparing the liquid crystal polymer resin / carbon fiber unidirectional tape, the present invention controls the resin extrusion temperature and speed to keep the arrangement direction of the resin molecules consistent with the arrangement direction of the fibers, so that the mechanical properties of the composite material along the fiber direction are significantly improved. At the same time, in the melt impregnation stage, through the catalytic reaction, the benzene ring groups on the surface of the carbon fiber and the groups on the rigid chain of the LCP resin undergo a chemical reaction to generate rigid side chains, which can significantly improve the mechanical properties of the composite material in the vertical fiber direction and improve the mechanical anisotropy of the LCP. At the same time, the generated groups have a fluorescent effect, so that the composite material can be used in the fields of decorations, safety signs, optical devices, etc. DETAILED DESCRIPTION
[0050] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0051] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0052] A liquid crystal polymer resin / carbon fiber unidirectional tape is prepared by using modified carbon fiber grafted with benzophenone groups and liquid crystal polymer resin containing benzophenone groups as raw materials to prepare a unidirectional tape containing tetraphenylethylene groups. The preparation steps include: S1. Preparation of modified carbon fiber grafted with benzophenone groups: surface treating the carbon fiber by interfacial modification technology to obtain a modified carbon fiber as shown in formula I; S2. Synthesis of a liquid crystal polymer resin containing a benzophenone group: preparing a low molecular weight liquid crystal polymer, and then preparing a liquid crystal polymer resin as shown in Formula II by melt copolymerization; S3. Preparation of liquid crystal polymer resin / carbon fiber unidirectional tape: preparing liquid crystal polymer resin / carbon fiber unidirectional tape by melt impregnation method; Formula I; Among them, the column is carbon fiber; Formula II; Among them, x=20%-50%, y=40%-70%, z=10%-20%, x+y+z=100%.
[0053] In some embodiments, in S2, the liquid crystal polymer resin containing a benzophenone group has a heteroatom group R, and its structure is shown in Formula III: Formula III; Among them, x=20%-50%, y=40%-70%, z=10%-20%, x+y+z=100%.
[0054] In some embodiments, the heteroatom group R is selected from any one of an amino group and a sodium sulfonate group.
[0055] In some embodiments, in S1, the specific steps are: S11, impregnating and cleaning the carbon fiber with a polar solvent to remove pollutants on the surface of the carbon fiber; S12, pre-oxidizing the surface of the carbon fiber with an oxidizing solution to increase the roughness of the carbon fiber surface and introduce oxygen-containing active groups; S13, adding a functional modifier and a catalyst to react fully to obtain a modified carbon fiber having a benzene ring structure on the surface.
[0056] In some embodiments, in S11, the polar solvent is selected from any one of ethanol, acetone, and petroleum ether.
[0057] In some embodiments, in S12, the oxidizing solution is selected from any one of a hydrogen peroxide solution, a potassium permanganate solution, and a sodium hypochlorite solution.
[0058] In some embodiments, in S12, the concentration of the oxidizing solution is 5-10 wt %.
[0059] In some embodiments, in S13, the concentration of the functional modifier is 1-5 wt %.
[0060] In some embodiments, in S13, the catalyst is 4-dimethylaminopyridine.
[0061] In some embodiments, in S13, the amount of the catalyst used is 0.01-0.03% of the amount of the functional modifier used.
[0062] In some embodiments, in S2, the specific steps are: S21, using bisphenol monomers and diacid monomers as raw materials and acetate compounds as catalysts to obtain low molecular weight liquid crystal polymers through esterification reaction; S22, heating the low molecular weight liquid crystal polymer to 300-350°C to carry out melt polymerization reaction to synthesize liquid crystal polymer resin.
[0063] In some embodiments, in S21, the bisphenol monomer is a mixture of 4,4-dihydroxybenzophenone and 2,7-dihydroxynaphthalene.
[0064] In some embodiments, in S21, the mass ratio of 4,4-dihydroxybenzophenone to 2,7-dihydroxynaphthalene is 1:1-5.
[0065] In some embodiments, in S21, the mass ratio of 4,4-dihydroxybenzophenone to 2,7-dihydroxynaphthalene is 1:1-4.
[0066] In some embodiments, in S21, the diacid monomer is selected from any one of terephthalic acid, 2-aminoterephthalic acid, and monosodium 2-sulfonate terephthalate.
[0067] In some embodiments, in S21, the diacid monomer is selected from any one of 2-aminoterephthalic acid and monosodium 2-sulfonateterephthalate.
[0068] In some embodiments, in S21, the mass ratio of the bisphenol monomer to the diacid monomer is 1:1-1.5.
[0069] In some embodiments, in S21, the mass ratio of the bisphenol monomer to the diacid monomer is 1:1-1.2.
[0070] In some embodiments, in S21, the acetate catalyst is selected from any one of calcium acetate, magnesium acetate, and zinc acetate.
[0071] In some embodiments, in S21, the mass of the acetate catalyst is 0.03-0.05% of the mass of the bisphenol monomer.
[0072] In some embodiments, in S21, the esterification reaction is carried out under an inert gas, and the inert gas is any one of nitrogen and argon.
[0073] In some embodiments, in S21, the esterification reaction temperature is 120-150°C.
[0074] In some embodiments, in S21, the esterification reaction time is 1-2 h.
[0075] In some embodiments, in S21, the esterification reaction is carried out under stirring conditions at a rotation speed of 500-100 rpm.
[0076] In some embodiments, in S22, the melt polymerization reaction temperature is 300-350°C.
[0077] In some embodiments, in S22, the melt polymerization reaction time is 30-60 min.
[0078] In some embodiments, in S3, the specific preparation steps are: S31, adjusting the tension roller pressure through the fiber yarn release system so that the modified carbon fiber prepared in step S1 is evenly stressed; and fully unfolding the modified carbon fiber prepared in step S1 through the fiber dispersion system and entering the fiber impregnation system; S32, adding the LCP resin and the catalyst prepared in step S2 into the resin discharging system, and heating to melt the LCP resin; S33, the molten LCP resin infiltrates into the fiber impregnation system, impregnates the modified carbon fiber, and obtains a prepreg tape; the thickness of the prepreg tape is determined by a cooling and shaping system, and then the prepreg tape is cut and rolled to obtain a liquid crystal polymer resin / carbon fiber unidirectional tape.
[0079] In some embodiments, in S3, the specific preparation steps of the liquid crystal polymer resin / carbon fiber unidirectional tape are: S31. Through the fiber yarn release system, adjust the tension roller pressure to 200-400N, so that the modified carbon fiber prepared in step S1 is evenly stressed and avoids bending; through the fiber dispersion system, adjust the heating temperature to 120-140°C, so that the modified carbon fiber prepared in step S1 is fully unfolded to avoid uneven dispersion and enter the fiber impregnation system.
[0080] S32. Add the LCP resin powder and catalyst powder prepared in step S2 into the resin discharging system, heat to melt the LCP resin, and control the melting temperature at 280-300° C. during the melting process. During the resin extrusion process, equip with a heat-insulating jacket to prevent the resin from rapidly cooling and solidifying, which may affect the liquid crystal orientation of the LCP resin.
[0081] In some embodiments, in S32, the catalyst is a mixture of titanium tetrachloride and zinc powder.
[0082] In some embodiments, in S32, the molar mass ratio of titanium tetrachloride to zinc powder is 1:2-2.2.
[0083] In some embodiments, in S32, the amount of catalyst added is 0.01-0.015% by mass of the LCP resin.
[0084] S33, the molten LCP resin infiltrates into the fiber impregnation system, impregnates the modified carbon fiber, and obtains a prepreg tape; the thickness of the prepreg tape is determined by a cooling and shaping system, and then the prepreg tape is cut and rolled to obtain a liquid crystal polymer resin / carbon fiber unidirectional tape.
[0085] In some embodiments, in S33, the working pressure of the cooling and shaping system is 5-10 MPa. During the preparation process, the excess resin on the fiber surface is squeezed out by pressure to make the product surface smooth and flat.
[0086] In some embodiments, in S33, the cooling and shaping system is a gradient cooling system, the temperature gradient is 250°C, 200°C, 150°C, 100°C, 50°C, 10°C, and the insulation time is 30-60min.
[0087] In some embodiments, the fiber impregnation system selects a curved flow channel type. The curved flow channel impregnation system can make the resin and fiber impregnated completely, and at the same time, under the action of the catalyst, the surface groups of the two have sufficient contact time and contact area to react and generate fluorescent groups, wherein the fiber and polymer rigid chains can effectively limit the free rotation of the fluorescent groups, thereby improving the luminescence performance.
[0088] A liquid crystal polymer resin / carbon fiber unidirectional tape prepared by the above method has a structure as shown in Formula IV: Formula IV; Among them, the column is carbon fiber; x=20%-50%, y=40%-70%, z=10%-20%, x+y+z=100%.
[0089] In some embodiments, the structure of the obtained liquid crystal polymer resin / carbon fiber unidirectional tape is as shown in Formula V: Formula V; Wherein, the column is carbon fiber, containing heteroatom groups R; x=20%-50%, y=40%-70%, z=10%-20%, x+y+z=100%.
[0090] In some embodiments, the heteroatom group R is selected from any one of an amino group and a sodium sulfonate group.
[0091] Example The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0092] Example 1 A liquid crystal polymer resin / carbon fiber unidirectional tape is prepared by the following steps: Step S1: First, the carbon fiber is impregnated with an ethanol solvent, cleaned, and the pollutants on the surface of the carbon fiber are removed; then, the surface of the carbon fiber is pre-oxidized with a 5wt% hydrogen peroxide solvent to introduce oxygen-containing active functional groups on its surface while increasing the surface roughness of the fiber, and then washed and dried; finally, a 1wt% concentration of 4-hydroxybenzophenone ethanol solution is used as a functional modifier and 4-dimethylaminopyridine is used as a catalyst (the amount is 0.01% of the mass of 4-hydroxybenzophenone), and the reaction is carried out at room temperature for 2h to obtain a modified carbon fiber grafted with a benzophenone group.
[0093] Step S2: Add 20kg of 4,4-dihydroxybenzophenone and 80kg of 2,7-dihydroxynaphthalene mixture, 100kg of 2-aminoterephthalic acid, and 30g of calcium acetate catalyst into a reaction kettle to carry out an esterification reaction. Nitrogen is required to replace the oxygen in the system during the reaction process. The reaction temperature is 120°C, the reaction time is 1h, and the mechanical stirring is performed at a stirring speed of 500 rpm. After the reaction is completed, a low molecular weight liquid crystal polymer is obtained. According to calculation, the mass ratio of 4,4-dihydroxybenzophenone to 2,7-dihydroxynaphthalene is 1:4; the mass ratio of bisphenol monomer to diacid monomer is 1:1; and the magnesium acetate catalyst is 0.03% of the bisphenol monomer.
[0094] The low molecular weight liquid crystal polymer is heated to 300°C and heated for a second time for melt polymerization. The reaction process requires vacuum to remove unreacted monomers. The reaction time is 30 minutes. After the reaction is completed, it is slowly cooled to room temperature, the LCP resin is taken out, and crushed to obtain resin powder.
[0095] Step S3: Compounding the modified carbon fiber obtained in step S1 and the LCP resin powder obtained in step S2 to prepare a liquid crystal polymer resin / carbon fiber unidirectional tape. During the preparation process, the tension of the fiber yarn release system is adjusted to 200N; the heating temperature of the fiber dispersion system is adjusted to 120°C, so that the carbon fiber is fully unfolded and evenly dispersed before entering the fiber impregnation system.
[0096] At the same time, 40kg of LCP resin powder, 1.33g of titanium tetrachloride crystal solid, and 2.66g of zinc powder were added to the resin discharging system, and the LCP resin was heated to melt. The melting temperature was controlled to be 280°C during the melting process. During the resin extrusion process, a heat preservation jacket was equipped to prevent the resin from solidifying rapidly and affecting the liquid crystal orientation of the LCP resin. According to calculations, the mass ratio of titanium tetrachloride to zinc powder is 1:2, and the two account for 0.01% of the mass of the LCP resin.
[0097] The fiber impregnation system selects a curved flow channel type, and the temperature is set to 280°C. The curved flow channel impregnation system can make the resin and fiber completely impregnated and fully react, and generate fluorescent groups, namely prepreg tapes.
[0098] Finally, the prepreg tape is passed through a cooling and shaping system with a working pressure of 5 MPa to determine the thickness. The cooling system is a gradient cooling system with a temperature gradient of 250°C, 200°C, 150°C, 100°C, 50°C, and 10°C. The insulation time is 30 minutes. After cutting and winding, the liquid crystal polymer resin / carbon fiber unidirectional tape is obtained.
[0099] Example 2 A liquid crystal polymer resin / carbon fiber unidirectional tape is prepared by the following steps: Step S1: First, the carbon fiber is impregnated with acetone solvent, cleaned, and the pollutants on the surface of the carbon fiber are removed; then, the surface of the carbon fiber is pre-oxidized with 7wt% potassium permanganate solvent to introduce oxygen-containing active functional groups on its surface and increase the surface roughness of the fiber, and then washed and dried; finally, 3wt% 4-hydroxybenzophenone ethanol solution is used as a functional modifier and 4-dimethylaminopyridine is used as a catalyst (the amount is 0.01% of the mass of 4-hydroxybenzophenone), and the reaction is carried out at room temperature for 4h to obtain a modified carbon fiber grafted with a benzophenone group.
[0100] Step S2: adding 20 kg of a mixture of 4,4-dihydroxybenzophenone and 60 kg of 2,7-dihydroxynaphthalene, 88 kg of monosodium 2-sulfonate terephthalate, and 32 g of a magnesium acetate catalyst into a reaction kettle to carry out an esterification reaction. Nitrogen is required to be passed through the reaction process to replace oxygen in the system. The reaction temperature is 140° C., the reaction time is 1.5 hours, and mechanical stirring is performed at a stirring speed of 800 rpm. After the reaction is completed, a low molecular weight liquid crystal polymer is obtained. According to calculation, the mass ratio of 4,4-dihydroxybenzophenone to 2,7-dihydroxynaphthalene is 1:3; the mass ratio of bisphenol monomer to diacid monomer is 1:1.1; and the magnesium acetate catalyst is 0.04% of the bisphenol monomer.
[0101] The low molecular weight liquid crystal polymer was heated to 320°C and heated for a second time for melt polymerization. The reaction process required vacuuming to remove unreacted monomers. The reaction time was 40 minutes. After the reaction was completed, it was slowly cooled to room temperature, the LCP resin was taken out, and crushed to obtain resin powder.
[0102] Step S3: Compounding the modified carbon fiber obtained in step S1 and the LCP resin powder obtained in step S2 to prepare a liquid crystal polymer resin / carbon fiber unidirectional tape. During the preparation process, the tension of the fiber yarn release system is adjusted to 300N, and the heating temperature of the fiber dispersion system is adjusted to 130°C, so that the carbon fiber is fully unfolded and evenly dispersed before entering the fiber impregnation system.
[0103] At the same time, 40kg of LCP resin powder, 1.55g of titanium tetrachloride crystal solid, and 3.25g of zinc powder were added to the resin discharging system, and the LCP resin was heated to melt. The melting temperature was controlled to be 300°C during the melting process. During the resin extrusion process, a heat preservation jacket was equipped to prevent the resin from solidifying rapidly and affecting the liquid crystal orientation of the LCP resin. According to calculations, the mass ratio of titanium tetrachloride to zinc powder is 1:2.1, and the two account for 0.012% of the mass of the LCP resin.
[0104] The fiber impregnation system selects a curved flow channel type, and the temperature is set to 300°C. The curved flow channel impregnation system can make the resin and fiber fully impregnated and react, and generate fluorescent groups, namely prepreg tapes.
[0105] Finally, the prepreg tape is cooled and set by a cooling system with a working pressure of 8 MPa to determine its thickness. The cooling system is a gradient cooling system with a temperature gradient of 250°C, 200°C, 150°C, 100°C, 50°C, and 10°C for 40 minutes. After cutting and winding, the liquid crystal polymer resin / carbon fiber unidirectional tape is obtained.
[0106] Example 3 A liquid crystal polymer resin / carbon fiber unidirectional tape is prepared by the following steps: Step S1: First, the carbon fiber is impregnated with petroleum ether solvent, cleaned, and the pollutants on the surface of the carbon fiber are removed; then, the surface of the carbon fiber is pre-oxidized with 10wt% sodium hypochlorite solvent to introduce oxygen-containing active functional groups on its surface and increase the surface roughness of the fiber, and then washed and dried; finally, 5wt% 4-hydroxybenzophenone ethanol solution is used as a functional modifier and 4-dimethylaminopyridine is used as a catalyst (the amount is 0.01% of the mass of 4-hydroxybenzophenone), and the reaction is carried out at room temperature for 6h to obtain a modified carbon fiber grafted with a benzophenone group.
[0107] Step S2: Add 50kg of 4,4-dihydroxybenzophenone and 50kg of 2,7-dihydroxynaphthalene mixture, 120kg of 2-sulfonated monosodium terephthalate, and 50g of zinc acetate catalyst into the reaction kettle to carry out an esterification reaction. Nitrogen is required to replace the oxygen in the system during the reaction process. The reaction temperature is 150°C, the reaction time is 2h, and the mechanical stirring is performed at a stirring speed of 1000 rpm. After the reaction is completed, a low molecular weight liquid crystal polymer is obtained. According to calculation, the mass ratio of 4,4-dihydroxybenzophenone to 2,7-dihydroxynaphthalene is 1:1; the mass ratio of bisphenol monomer to diacid monomer is 1:1.2; and the magnesium acetate catalyst is 0.05% of the bisphenol monomer.
[0108] The low molecular weight liquid crystal polymer is heated to 350°C and heated for a second time for melt polymerization. The reaction process requires vacuum to remove unreacted monomers. The reaction time is 60 minutes. After the reaction is completed, it is slowly cooled to room temperature, the LCP resin is taken out, and crushed to obtain resin powder.
[0109] Step S3: Compounding the modified carbon fiber obtained in step S1 and the LCP resin powder obtained in step S2 to prepare a liquid crystal polymer resin / carbon fiber unidirectional tape. During the preparation process, the tension of the fiber yarn release system is adjusted to 400N, and the heating temperature of the fiber dispersion system is adjusted to 140°C, so that the carbon fiber is fully unfolded and evenly dispersed before entering the fiber impregnation system.
[0110] At the same time, 40kg of LCP resin powder, 1.88g of titanium tetrachloride crystalline solid, and 4.16g of zinc powder were added to the resin discharging system, and the LCP resin was heated to melt. The melting temperature was controlled to be 300°C during the melting process. During the resin extrusion process, a heat preservation jacket was equipped to prevent the resin from solidifying rapidly and affecting the liquid crystal orientation of the LCP resin. According to calculations, the mass ratio of titanium tetrachloride to zinc powder is 1:2.2, and the two account for 0.015% of the mass of the LCP resin.
[0111] The fiber impregnation system is of curved channel type, and the temperature is set to 300°C. The curved channel impregnation system can make the resin and fiber impregnation completely and fully react, and generate fluorescent groups, namely prepreg tapes.
[0112] Finally, the prepreg tape is cooled and set by a cooling system with a working pressure of 10 MPa to determine its thickness. The cooling system is a gradient cooling system with a temperature gradient of 250°C, 200°C, 150°C, 100°C, 50°C, and 10°C for 60 minutes. After cutting and winding, the liquid crystal polymer resin / carbon fiber unidirectional tape is obtained.
[0113] Example 4 Example 4 is basically the same as Example 1, with the main difference being that in step S2, 2-aminoterephthalic acid is replaced by terephthalic acid.
[0114] Comparative Example 1 Comparative Example 1 is substantially the same as Example 1, with the main difference being that in step S1, the carbon fiber is not modified, and in step S3, the carbon fiber without pretreatment is directly used.
[0115] Comparative Example 2 Comparative Example 2 is basically the same as Example 2, with the main difference being that in step S3, the modified carbon fiber grafted with benzophenone groups obtained in S1 and the LCP resin obtained in S2 are compounded, and no catalyst is added during the preparation of the liquid crystal polymer resin / carbon fiber unidirectional tape.
[0116] Comparative Example 3 Comparative Example 3 is substantially the same as Example 1, with the main difference being that in step S2, commercially available Victrex PEEK resin masterbatch is used.
[0117] In step S3, the modified carbon fiber grafted with benzophenone groups obtained in step S1 and the PEEK resin masterbatch obtained in step S2 are used to prepare a PEEK / carbon fiber unidirectional tape. It is found in the experiment that under the same process conditions as in Example 1, the PEEK resin cannot be melted.
[0118] Test Example 1 The appearance of the unidirectional tapes prepared in Examples 1-4 and Comparative Examples 1-3 was observed, the luminescence of the unidirectional tapes was observed under a 365nm ultraviolet lamp, and the mechanical properties were tested using a universal mechanical testing machine (electronic universal testing machine CMT6103). The test method refers to the standard ASTM D3039 Standard Test Method for Tensile Properties of Polymer-based Composite Materials. The test results are shown in Table 1: Table 1
[0119] As can be seen from Examples 1-3, with the increase in the degree of oxidation of the carbon fiber and the increase in the content of 4,4-dihydroxybenzophenone monomers on the polymer molecular chain, the number of unidirectional fluorescent groups increases, which is manifested as more surface fluorescent areas. At the same time, due to the increase in covalent bonds, the polymer chain and the carbon fiber have a stronger bond, which is manifested as enhanced mechanical properties. In Example 4, since the liquid crystal polymer resin does not contain heteroatoms, it is impossible to produce intermolecular effects through heteroatoms and groups on the modified carbon fiber, so the strength is reduced, but due to the bonding between the modified carbon fiber and the benzophenone on the liquid crystal polymer, the overall strength is still high.
[0120] Comparative Example 1 Compared with Example 1, the unmodified carbon fiber is easy to aggregate in the resin matrix, resulting in uneven fiber dispersion, incomplete resin impregnation, dry yarn phenomenon, and the fiber is easy to be pulled out of the resin in the tensile test, and the mechanical properties of the test specimen are poor. At the same time, since the fiber is unmodified, it cannot react chemically with the resin, and only a small amount of self-polymerization reaction between the resins is generated to generate a very small amount of fluorescent groups.
[0121] It can be seen from Example 2 and Comparative Example 2 that without the presence of a catalyst, fluorescent groups cannot be generated in the system, and the polymer molecular chains and the carbon fiber surface act mainly through hydrogen bonds and π-π bonds. The mechanical properties of the splines of Comparative Example 2 are worse than those of the covalently bonded splines of Example 2.
[0122] Comparative Example 3 Compared with Example 1, at the same melting temperature (300°C), PEEK resin cannot melt, has poor fluidity, and cannot wet carbon fiber. Compared with LCP resin, the processing conditions are more complicated. Therefore, in the process of synthesizing the rigid chain of LCP resin, the present invention introduces heteroatom-containing groups on the polymer chain through molecular structure design, which can produce strong intermolecular effects with the groups on the modified carbon fiber. At the same time, the melting temperature and fluidity of the resin are significantly improved, which can reduce the processing temperature and difficulty of the composite material.
[0123] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, change of structural morphology, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0124] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0125] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0126] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
[0127] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A liquid crystal polymer resin / carbon fiber unidirectional tape, characterized in that: The unidirectional tape is prepared by compounding modified carbon fibers grafted with benzophenone groups and liquid crystal polymer resin containing benzophenone groups, and the prepared unidirectional tape contains tetraphenylethylene groups.
2. The liquid crystal polymer resin / carbon fiber unidirectional tape according to claim 1, characterized in that: The structure of the modified carbon fiber grafted with benzophenone groups is shown in Formula I, and the structure of the liquid crystal polymer resin containing benzophenone groups is shown in Formula II. Formula I; Among them, the column is a fiber; Formula II; Among them, x=20%-50%, y=40%-70%, z=10%-20%, x+y+z=100%.
3. The liquid crystal polymer resin / carbon fiber unidirectional tape according to claim 1, characterized in that: Its structure is shown in Formula IV: Formula IV; Among them, the column is fiber, x=20%-50%, y=40%-70%, z=10%-20%, x+y+z=100%.
4. The liquid crystal polymer resin / carbon fiber unidirectional tape according to claim 1, characterized in that: The liquid crystal polymer resin further contains a heteroatom group. Preferably, the heteroatom group is selected from any one of an amino group and a sodium sulfonate group.
5. A method for preparing the liquid crystal polymer resin / carbon fiber unidirectional tape according to any one of claims 1 to 4, characterized in that: The steps include: S1. Preparation of modified carbon fiber grafted with benzophenone groups: surface treating the carbon fiber by interfacial modification technology to obtain a modified carbon fiber as shown in formula I; S2. Synthesis of a liquid crystal polymer resin containing a benzophenone group: preparing a low molecular weight liquid crystal polymer, and then preparing a liquid crystal polymer resin as shown in Formula II by melt copolymerization; S3. Preparation of liquid crystal polymer resin / carbon fiber unidirectional tape: Liquid crystal polymer resin / carbon fiber unidirectional tape is prepared by melt impregnation method.
6. The method for preparing the liquid crystal polymer resin / carbon fiber unidirectional tape according to claim 5, characterized in that: The step S1 comprises the following steps: S11, impregnating and cleaning the carbon fiber with a polar solvent; S12, pre-oxidizing the surface of the carbon fiber with an oxidizing solution; S13, adding a functional modifier and a catalyst to fully react to obtain modified carbon fiber.
7. The method for preparing the liquid crystal polymer resin / carbon fiber unidirectional tape according to claim 6, characterized in that: In S11, the polar solvent is selected from any one of ethanol, acetone, and petroleum ether; In S12, the oxidizing solution is selected from any one of a hydrogen peroxide solution, a potassium permanganate solution, and a sodium hypochlorite solution; In S12, the concentration of the oxidizing solution is 5-10 wt%; In S13, the functional modifier is 4-hydroxybenzophenone; In S13, the concentration of the functional modifier is 1-5 wt %; In S13, the catalyst is 4-dimethylaminopyridine; In S13, the amount of the catalyst used is 0.01-0.03% of the amount of the functional modifier used.
8. The method for preparing the liquid crystal polymer resin / carbon fiber unidirectional tape according to claim 5, characterized in that: The step S2 comprises the following steps: S21, using bisphenol monomers and diacid monomers as raw materials and acetate compounds as catalysts to obtain low molecular weight liquid crystal polymers through esterification reaction; S22, heating the low molecular weight liquid crystal polymer to 300-350° C. to perform melt polymerization reaction to synthesize a liquid crystal polymer resin; The bisphenol monomer is a mixture of 4,4-dihydroxybenzophenone and 2,7-dihydroxynaphthalene; The mass ratio of 4,4-dihydroxybenzophenone to 2,7-dihydroxynaphthalene is 1:1-5, preferably 1:1-4; The diacid monomer is selected from any one of terephthalic acid, 2-aminoterephthalic acid, and 2-sulfonato terephthalic acid monosodium, preferably any one of 2-aminoterephthalic acid and 2-sulfonato terephthalic acid monosodium; The acetate catalyst is selected from any one of calcium acetate, magnesium acetate and zinc acetate; The mass ratio of the bisphenol monomer to the diacid monomer is 1:1-1.5, preferably 1:1-1.2; The mass of the acetate catalyst is 0.03-0.05% of the mass of the bisphenol monomer.
9. The method for preparing the liquid crystal polymer resin / carbon fiber unidirectional tape according to claim 5, characterized in that: The step S3 comprises the following steps: S31, adjusting the tension roller pressure through the fiber yarn release system so that the modified carbon fiber prepared in step S1 is evenly stressed; and fully unfolding the modified carbon fiber prepared in step S1 through the fiber dispersion system and entering the fiber impregnation system; S32, adding the liquid crystal polymer resin prepared in step S2 and the catalyst into the resin discharging system, and heating to melt the liquid crystal polymer resin; S33, the molten liquid crystal polymer resin infiltrates into the fiber impregnation system, impregnates the modified carbon fiber, and obtains a prepreg tape; the thickness of the prepreg tape is determined by a cooling and shaping system, and then the liquid crystal polymer resin / carbon fiber unidirectional tape is obtained through cutting and winding.
10. The method for preparing the liquid crystal polymer resin / carbon fiber unidirectional tape according to claim 9, characterized in that: The tension adjustment range of the fiber yarn release system is 200-400N; The heating temperature of the fiber dispersion system is 120-140°C; The melting temperature is 280-300°C; The catalyst is a mixture of titanium tetrachloride and zinc powder; The mass ratio of titanium tetrachloride to zinc powder is 1:2-2.2; The amount of the catalyst added is 0.01-0.015% of the mass of the liquid crystal polymer resin; The heating temperature of the fiber impregnation system is 280-300°C; The working pressure of the cooling and shaping system is 5-10MPa.
